One-step additive crosslinking of conjugated polyelectrolyte interlayers: improved lifetime and performance of solution-processed OLEDs - Stolz, Sebastian; Petzoldt, Martin; Freudenberg, Jan; Bunz, Uwe H. F.; Lemmer, Uli; Hamburger, Manuel (Journal of materials chemistry. C, Materials for optical and electronic devices, 2016)
We crosslink an amino-functionalized polyfluorene by the solvent additive 1,8-diiodooctane (DIO). DIO remains in the film after drying of the main solvent and chemically binds to the amino-side groups after a low temperature annealing step, rendering the polyfluorene film insoluble in non-polar solvents. We correlate the amount of DIO, the reduction of operational voltage and increase in lifetime of solution-processed OLEDs. We demonstrate a fully solution-processed device using the crosslinked polyfluorene electron injection layer and an inkjet-printed Ag top electrode.